Compressive strength forecasting of rubberised lightweight foamed concrete with fresh density of 1350kg/m3 during the hardening process utilising elastic wave method - Ngui, Jun Kit (2023)
The issue of tyre waste has grown as a significant environmental concern, caused mainly by annual population expansion. In modern times, lightweight foamed concrete is widely used across various sectors. Additionally, there is a growing trend of reusing tyre waste into crumb rubber, which replaces fine aggregate in the production of rubberised lightweight foamed concrete. It is essential to do the compressive strength test on the existing structure created using rubberised lightweight foamed concrete. Nevertheless, the current approach to assessing the compressive strength of preexisting structures continues to be invasive. The primary objective of this research is to assess the compressive strength of rubberised lightweight foam concrete using an innovative, non-destructive test method. The flexural strength and splitting tensile strength tests were conducted to analyse further the tensile strength of the rubberised lightweight foamed concrete. This study investigates a sample of rubberised lightweight foamed concrete using the destructive test method and non-destructive test method. The compressive strength of rubberised lightweight foamed concrete is determined through the application of loading until failure occurs, utilising a compression test machine within the framework of the destructive test method. The study utilises the non-destructive test method of ultrasonic pulse velocity of the elastic wave method. The alteration in P-wave properties has been investigated to establish a correlation with the compressive strength obtained from the destructive test. The parameter of P-wave amplitude exhibits a strong positive correlation with compressive strength, as indicated by a regression coefficient greater than 0.8. The correlation between the velocity of the P-wave parameter and compressive strength exhibits a regression degree below 0.8. This indicates that the wave amplitude is more suitable to forecast the compressive strength of rubberised lightweight foamed concrete than wave velocity since it exhibits a substantially higher degree of regression. In summary, it can be concluded that rubberised lightweight foam concrete has favourable characteristics that make it a viable option for construction purposes. The higher regression degree of the non-destructive test method enables an adequate prediction of the compressive strength of rubberised lightweight foam concrete.